THE STATUS OF SCIENTIFIC RESEARCH AT TRUNG VUONG HOSPITAL, HO CHI MINH CITY IN THE PERIOD 2019 – 2024 AND INFLUENCING FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of scientific research activities, and analyze influencing factors at Trung Vuong Hospital, Ho Chi Minh City during the period 2019-2024.Subject and method: Mixed-method research combining quantitative and qualitative approaches. Collecting data on the current state of scientific research through a survey of 316 healthcare workers and examined research records from 2019-2024. Influencing factors were explored through eight in-depth interviews and four focus group discussions.Results: There were 55 research projects, and 14 scientific publications during the period 2019-2024, 64.3% of which were published in domestic journals. Mean age of participants was 36.6±9.2 years, and 71.5% were females. The rate of participation in scientific research is 38.9%. Furthermore, there was a statistically significant difference between age, educational attainment, work unit, and position, and the status of participation in scientific research (p
Keywords: Science research, Trung Vuong Hospital, influcencing factors